Silencing RBBP6 (Retinoblastoma Binding Protein 6) sensitizes breast cancer cells to staurosporine and camptothecin-induced cell death - Moela, Pontsho (My University, 2014)
Retinoblastoma Binding Protein 6 (RBBP6) is a multi-domain protein that uses its ring finger domain to interact with p53 and pRb tumour suppressor genes. The mechanism by which RBBP6 uses to degrade p53 is still unknown. Nonetheless, it is well known that RBBP6 promotes cell proliferation in several cancers by negatively regulating p53 via its E3 ubiquitin ligase activity (Ntwasa, 2008). Degradation of p53 by RBBP6 may compromise p53-mediated apoptosis in breast cancer. This study is intended to investigate the potential applications of RNA interference (RNAi) to block RBBP6 expression as well as its subsequent effect on cell growth and apoptosis. To achieve these methodologies, the following techniques were used: RT-PCR, western blotting, xCELLigence system and flow cytometry. Our studies indicate that the knockdown of RBBP6 expression by siRNA modulates p53 gene involved in cell death pathways and apoptosis, showing statistically significant gene expression differences. RBBP6siRNA significantly reduced cell index (CI) compared to the control samples and we observed an inhibition of cellular proliferation in the interval of between 24 and 48 h, as shown in the data obtained by dynamic evaluation using the xCELLigence System. These results were further confirmed by flow cytometry which showed some apoptotic activity. About 20.7% increase in apoptosis was observed in cells co-treated with RBBP6 siRNA and camptothecin when compared to camptothecin-only whereas in siRBBP6 and Staurosporine treated there was only 8.8% increase in apoptosis. These findings suggest that silencing RBBP6 may be a novel strategy to promote staurosporine- and camptothecin-induced apoptosis in breast cancer cells. Keywords: Retinoblastoma Binding Protein 6, staurosporine, camptothecin
A dissertation submitted to the Faculty of Science, University of Witwatersrand, Johannesburg, in partial fulfilment of the requirements for the degree of Master of Science. Gauteng, Johannesburg, 2013.
Keywords: Breast - Cancer.; Proteins.; Cell death.